The Effect of Public Share Ownership, Capital Intensity, and Firm Age on Tax Aggressiveness with Firm Size as a Moderating Variable - I Putu Agus Dharmayasa; I Putu Gede Diatmika; Nyoman Ari Surya Dharmawan (Dinasti Publisher, 2025)
This study aims to analyze the effect of public share ownership, capital intensity, and firm age on tax aggressiveness, with firm size as a moderating variable. A quantitative research design was employed, using a population of manufacturing companies listed on the Indonesia Stock Exchange (IDX) during the period 2021–2023. The sample was selected using purposive sampling, resulting in 36 companies that met the criteria, with three years of observation yielding a total of 108 financial statement data points. Data were collected through documentation studies and analyzed using Moderated Regression Analysis (MRA) with panel data. The findings of this study indicate that public share ownership and firm size have a significant negative effect on tax aggressiveness, while capital intensity has a significant positive effect. Furthermore, firm size strengthens the negative influence of public share ownership and firm age on tax aggressiveness, while it weakens the positive influence of capital intensity on tax aggressiveness.